Anaerobic Composting of Farmyard Manure as Affected by Chicken Manure, Urea and Waste Water (University of Khartoum Journal of Agricultural Sciences, 2023)
the objectives of this study were to investigate the stage ofmaturity and to determine nutrient contents of farmyard manure (FYM)composted with 2% chicken manure (CHM), 1% urea, and 25% wastewater, during the summer seasons of 1997 and 1998. The treatments werereplicated thrice in a completely randomized design. The total number ofexperimental units was repeated eight times for destructive sampling at 15days intervals for a period of four months. The treatments were buried inauger holes (90-cm depth) and samples were collected and chemicallyanalysed. The analysis included crude fibre, cellulose, starch, calcium,magnesium, sodium, nitrogen, phosphorus and potassium contents. Thestage of maturity of FYM was measured by the biodegradation of crudefibre, cellulose and starch contents which decreased significantly (P≤0.005). The rate of crude fibre decomposition was highest in ureafollowed by CHM and waste water. The rate of cellulose decompositionof both urea and waste water treatments was significantly higher than theCHM and control treatments. Starch disappeared in the 12th week in CHMtreatment and in the 14th week in waste water treatment. CHM treatmentwas superior in calcium release followed by waste water and ureatreatments. The lowest sodium was detected in waste water treatmentfollowed by both CHM and urea. Waste water, however, showed thehighest nitrogen and phosphorus contents compared to the othertreatments. Potassium content was the highest in CHM followed by ureaand waste water. In conclusion, the best compost ripening time was afterthree months when its nutritive value was the highest and the physicalproperties were best
Keywords: Farmyard manure; chicken manure; urea; waste water